Is the Chinese growth miracle built to last? - Eswar S. Prasad (Institute for the Study of Labor (IZA), 2007)
Is the Chinese growth miracle - a remarkably high growth rate sustained for over two decades - likely to persist or are the seeds of its eventual demise contained in the policies that have boosted growth? For all its presumed flaws, the particular approach to macroeconomic and structural policies that has been adopted by the Chinese government has helped to deliver high productivity and output growth, along with a reasonable degree of macroeconomic stability. In tandem with a benign international environment, this approach makes it unlikely that the economy will face a collapse in growth. But there comes a point when the policy distortions needed to maintain this approach could generate imbalances, impose potentially large welfare costs, and themselves become a source of instability. The traditional risks faced by emerging market economies, especially those related to having an open capital account, do not loom large in the case of China. In the process of securing protection against external risks, however, Chinese policymakers may have increased the risks of internal instability. There are a number of factors that could trigger unfavorable economic dynamics that, even if they don't rise to the level of a crisis, could have serious adverse repercussions on growth and welfare. The flexibility and potency of macroeconomic tools to deal with such negative shocks is constrained by the panoply of policies that has supported growth so far.
Keywords: 330; Wirtschaftswachstum; Wirtschaftspolitik; Wirkungsanalyse; China